Timing of Novel Drug 1A-116 to Circadian Rhythms Improves Therapeutic Effects against Glioblastoma - Laura Lucía Trebucq; Georgina Alexandra Cardama; Pablo Lorenzano Menna; Diego Andrés Golombek; Juan José Chiesa; Luciano Marpegan (MDPI AG, 2021)
The Ras homologous family of small guanosine triphosphate-binding enzymes (GTPases) is critical for cell migration and proliferation. The novel drug 1A-116 blocks the interaction site of the Ras-related C3 botulinum toxin substrate 1 (RAC1) GTPase with some of its guanine exchange factors (GEFs), such as T-cell lymphoma invasion and metastasis 1 (TIAM1), inhibiting cell motility and proliferation. Knowledge of circadian regulation of targets can improve chemotherapy in glioblastoma. Thus, circadian regulation in the efficacy of 1A-116 was studied in LN229 human glioblastoma cells and tumor-bearing nude mice. Methods. Wild-type LN229 and BMAL1-deficient (i.e., lacking a functional circadian clock) LN229E1 cells were assessed for rhythms in TIAM1, BMAL1, and period circadian protein homolog 1 (PER1), as well as Tiam1, Bmal1, and Rac1 mRNA levels. The effects of 1A-116 on proliferation, apoptosis, and migration were then assessed upon applying the drug at different circadian times. Finally, 1A-116 was administered to tumor-bearing mice at two different circadian times. Results. In LN229 cells, circadian oscillations were found for BMAL1, PER1, and TIAM1 (mRNA and protein), and for the effects of 1A-116 on proliferation, apoptosis, and migration, which were abolished in LN229E1 cells. Increased survival time was observed in tumor-bearing mice when treated with 1A-116 at the end of the light period (zeitgeber time 12, ZT12) compared either to animals treated at the beginning (ZT3) or with vehicle. Conclusions. These results unveil the circadian modulation in the efficacy of 1A-116, likely through RAC1 pathway rhythmicity, suggesting that a chronopharmacological approach is a feasible strategy to improve glioblastoma treatment.